2015
DOI: 10.1097/ccm.0000000000000626
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Predicts Outcome in Patients With Postanoxic Coma During Mild Therapeutic Hypothermia*

Abstract: Electroencephalogram allows reliable prediction of both good and poor neurologic outcome of patients with postanoxic encephalopathy treated with mild therapeutic hypothermia within 24 hours after cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
75
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 39 publications
5
75
1
Order By: Relevance
“…This is explained by an evolution of the EEG toward less specific patterns beyond 24 hours. The results of this study are partly in accordance with our own 3,4,19 and other 9,15-17,23,24 previous reports. However, current predictive values are higher, without false positives for unfavorable EEG patterns at 24 hours for poor outcome prediction.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…This is explained by an evolution of the EEG toward less specific patterns beyond 24 hours. The results of this study are partly in accordance with our own 3,4,19 and other 9,15-17,23,24 previous reports. However, current predictive values are higher, without false positives for unfavorable EEG patterns at 24 hours for poor outcome prediction.…”
supporting
confidence: 83%
“…1,2 Early identification of patients without potential for recovery of brain function may prevent inappropriate continuation of medical treatment. [3][4][5][6][7][8][9][10][11][12][13] A bilaterally absent somatosensory evoked potential (SSEP) is currently the most reliable predictor of poor outcome, but its sensitivity to detect poor outcome is low. 10,14 Pathologic EEG patterns, such as burst-suppression and epileptiform patterns, have been associated with poor outcome, but not invariably so.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The primary goal was to explore if infraslow activity was present in patients with a postanoxic encephalopathy and to further our understanding of burst clusters in patients with burst-suppression with identical bursts. At present, EEG features as reactivity, amplitude, continuity, dominant frequency, and characteristics of the burstsuppression patterns have shown to be strongly predictive of outcome in patients with postanoxic encephalopathy (Cloostermans et al 2012;Hofmeijer et al 2014b;Rossetti et al 2010;Tjepkema-Cloostermans et al 2015). Although amplitudes of the infraslow activity larger than 35 V or a MI Ͼ 0.016 were always associated with poor outcome, we did not explore if these features have additional diagnostic value; this will be the topic of a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that in these patients irreversible brain damage is associated with persistent isoelectric or severely depressed EEG activity (Cloostermans et al 2012;Tjepkema-Cloostermans et al 2015). In some patients, isoelectric recordings were interpuncted with stereotypical bursts, resulting in "burst-suppression with identical bursts" (Hofmeijer et al 2014b), that may appear in clusters.…”
mentioning
confidence: 99%